Interaction Diagram of Hollow-Crossed Reinforced Concrete Columns Undergoing Biaxial Bending Using the Closed Polygon Method - Yudi Susetyo; Agus Maryoto; Nanang Gunawan (Engineering Faculty, UNSOED, 2025)
Design of reinforced concrete columns in certain conditions requires a hollow cross-section for plumbing lines and cable lines. This hollow cross-section requires more careful analysis calculations. Because construction planning practices are more complicated if always calculated manually. So this study aims to develop a universal analysis calculation method regarding the interaction diagram of hollow columns using a computer program. Column strength analysis uses the strain compatibility method. Analysis of cross-section properties uses the closed polygon geometry method. Where the vertex points of the cross-section polygon are labeled numerically. The numbering of the exterior boundary vertex points is arranged in the order following the counterclockwise direction, while the internal boundary is arranged in the order of the clockwise direction. The calculation results of this method are compared with the calculation results of the PCA-COL program in the case of the same column. The results of the NMSE performance index test for 3 models are distinguished by 3 different cross-section rotation angles, each 00, 300, and 450. For the axial force capacity of the 3 models, the respective NMSE performance indexes are obtained; 0.0000212066, 0.0000244858, 0.0000300786. While the NMSE performance index test for the bending moment capacity of the 3 models was obtained; 0.045109796, 0.048488446, 0.04994925. All the results are close to zero, so the calculation method has high accuracy.